2020
DOI: 10.3390/ijerph17197154
|View full text |Cite
|
Sign up to set email alerts
|

How Will the Future of Work Shape the OSH Professional of the Future? A Workshop Summary

Abstract: Rapid and profound changes anticipated in the future of work will have significant implications for the education and training of occupational safety and health (OSH) professionals and the workforce. As the nature of the workplace, work, and the workforce change, the OSH field must expand its focus to include existing and new hazards (some yet unknown), consider how to protect the health and well-being of a diverse workforce, and understand and mitigate the safety implications of new work arrangements. Prepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…In addition, AI systems integrated into individual workstations could turn off lights, personal comfort devices, and other electronic devices when the presence of the worker is not noted as a means of conserving energy [ 42 ]. Future study is needed to explore the transactions that occur among a worker, the workspace, and an AI system to better understand these interplays and the implications of worker health, work performance, and other organizational or environmental impacts within future office work contexts [ 26 ]. Such a multifaceted approach could result in robust, efficacious workplace worker health solutions [ 20 , 34 ] with additional far-reaching benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AI systems integrated into individual workstations could turn off lights, personal comfort devices, and other electronic devices when the presence of the worker is not noted as a means of conserving energy [ 42 ]. Future study is needed to explore the transactions that occur among a worker, the workspace, and an AI system to better understand these interplays and the implications of worker health, work performance, and other organizational or environmental impacts within future office work contexts [ 26 ]. Such a multifaceted approach could result in robust, efficacious workplace worker health solutions [ 20 , 34 ] with additional far-reaching benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The plethora of health and performance issues associated with office work are likely to continue and expand in future work and workplaces [ 21 , 26 ]; thus, it is ever important to identify solutions to the challenges of mitigating risk and improving well-being within office work [ 27 ]. Environmental modifications such as sit-stand desks have been found to reduce sedentary work behavior in the short term, but no studies examining these modifications have demonstrated long-term effectiveness of reducing sedentary behavior [ 28 ] nor any effects in reducing pain-related disability in office workers [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature to demonstrate that the future of work will have increasingly profound effects on the jobs that workers around the world perform every day [1][2][3][4][5][6][7]. These changes will affect not only the nature of work but also the workplace and the workforce, and existing paradigms of worker health, safety, and well-being will need to shift to meet new challenges for worker protections [8][9][10][11]. Many of these changes will Int.…”
Section: Introductionmentioning
confidence: 99%
“…The need for an expanded focus for occupational safety and health (OSH) to prepare for such changes anticipated in the future of work has been well documented [8,11,16,[19][20][21]. One model for an expanded focus for OSH (Figure 1) calls for broadening the traditional OSH domains, which previously focused on evaluating workplace exposures and hazards and developing risk-prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation